Clinical use of calcium sulphate in bone regeneration therapy: Case report - Radulović Milan 1; Brković Božidar (Serbian Medical Society - Dental Section, Belgrade, 2003)
It is well known that a variety of materials has been used to fill bone defects after oral surgery procedures. In this study, we showed 2 patients with large osseus defects after oral surgery procedures which were filled with calcium sulphate. The use of this alloplastic material should indicate on effective bone regeneration therapy.